Delirium in critical care unit patients: prevalence and associated risk factors - Abdul Rashid, Ujala; Fatima, Zoha; Nasim, Umara; Muattar, Hafiza Amina (Journal of the Pakistan Medical Association, 2023)
A large number of critically ill patients experience physical and mental distress, resulting from systemic illness, multiple interventions, and environmental factors, during their stay in the Intensive Care Unit (ICU). Delirium is a common medical problem related to prolonged critical care. ICU delirium is linked to higher mortality as well as morbidity. The majority of patients suffering from delirium in the ICU experience hypoactive delirium, which remains relatively undiagnosed. Multiple tools have been devised for ICU delirium screening and early diagnosis. This short report aimed to assess the prevalence of delirium using a validated screening tool in medical ICU patients and determine the associated modifiable and non-modifiable risk factors. Keywords: Psychomotor agitation, Anxiety, Delirium, critical illness.